The impact of price, time, trust, and convenience on customer purchase behavior on shopee platform in east coast Malaysia - Muhammad Ali Asghar Amirullah; Nurul Amirah Norrizan; Nursyazwani Mohamad Riah; Salwa Subri (2023)
Shopee is one of the leading e-commerce platforms in Malaysia and the largest e-commerce in southeast Asia in 2020. Despite fierce competition in the e-commerce space, Shopee has grown aggressively across the Southeast Asia region over the past few years. The successful expansion of his business may be due to its deep competitive advantage. This study was to examine the main factors that impact customer attitudes around the east coast states of Malaysia namely Kelantan, Terengganu and Pahang towards the use of Shopee. The four factors that have an impact are price, time, trust and convenience. Survey questionnaires are used for data collection. A total of 385 Shopee users from the east coast residents of Malaysia namely Kelantan, Terengganu and Pahang responded to the survey. The results of the study have revealed that price, time, trust and convenience have had a positive impact on influencing customer attitudes towards Shopee users in Malaysia. This study provides Shopee with valuable insights and guidance on customers' perceptions of Shopee, leading to better customer satisfaction.